Elaboración de un plan de contingencia para los sistemas informáticos de las juntas administradoras de agua potable de la parroquia de Guaytacama. Caso de estudio Junta Administradora de Agua Potable Pilacoto. - Casa Guayta, Carlos Welington (2020)
The present project proposes the “DEVELOPMENT OF A CONTINGENCY PLAN FOR THE COMPUTER SYSTEMS OF THE DRINKING WATER MANAGEMENT BOARDS OF THE PARISH OF GUAYTACAMA - CASE STUDY OF THE PILACOTO DRINKING WATER MANAGEMENT BOARD”. This guide will allow for adequate risk management, as well as the implementation recovery strategies for information technology, which will ensure the continuity of technological and computer services, in this case of the Pilacoto Board, if they were interrupted by any type of incident; which can later be replicated in the other Drinking Water Management Boards of Guaytacama.